Hubungan Antara High Order Thinking Skills dan Kemampuan Literasi Sains Mahasiswa Pendidikan Biologi: (The Relationship Between High Order Thinking Skills and Science Literacy Abilities of Biology Education Students) - Rahmatia Thahir; Nurul Magfirah; Anisa Anisa (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2021)
Higher Order Thinking Skills can develop the ability to investigate problems, ask questions, pose challenging answers and discover new information. Higher order thinking skills are one of the factors that affect scientific literacy skills. Literacy skills are not enough just to be able to read, more than that, students are expected to have the ability to reason and competence, be active, creative, and critical of what they know. The purpose of this study was to analyze the relationship between higher order thinking skills and scientific literacy skills of Biology Education students, University of Muhammadiyah Makassar. This research includes correlational descriptive research which is carried out in the even semester of the 2020-2021 academic year. The instrument in this study was in the form of student learning outcomes tests. Then from student learning outcomes, a score will be given based on the ability to complete the HOTS test questions while the scientific literacy ability is assessed using a scoring rubric. there is a positive relationship between higher order thinking skills and scientific literacy skills of biology education students at the University of Muhammadiyah Makassar with a correlation value of 0.370. The value of learning outcomes with the average categorization of high order thinking skills is 56.7 and the average scientific literacy ability is 66.7. Abstrak. Higher Order Thinking Skils dapat menumbuhkembangkan kemampuan untuk menyelidiki masalah, mengajukan pertanyaan, mengajukan jawaban yang menantang dan menemukan informasi baru. Kemampuan berpikir tingkat tinggi merupakan salah satu faktor yang mempengaruhi kemampuan literasi sains. Kemampuan literasi tidak cukup dengan bisa membaca saja, lebih daripada itu mahasiswa diharapkan memiliki kemampuan bernalar dan kompetensi, aktif, kreatif, serta kritis terhadap apa yang diketahuinya. Tujuan dari penelitian ini adalah untuk menganalisis hubungan antara higher order thinking skills dan kemampuan literasi sains mahasiswa Pendidikan Biologi Universitas Muhammadiyah Makassar. Penelitian ini termasuk penelitian deskriptif korelasional Â yang dilaksanakan pada semester genap tahun akademik 2020-2021. Instrument dalam penelitian ini berupa tes hasil belajar mahasiswa. Kemudian dari hasil belajar mahasiswa akan diberikan penskoran berdasarkan kemampuan menyelesaikan soal tes HOTS sedangkan kemampuan literasi sains dinilai dengan menggunakan rubrik penskoran. terdapat hubungan yang positif antara higher order thinking skills dan kemampuan literasi sains mahasiswa pendidikan biologi Universitas Muhammadiyah Makassar dengan nilai korelasi sebesar 0,370. Nilai hasil belajar dengan pengkategorian rata-rata higher order thinking skills sebesar 56,7 dan rata-rata kemampuan literasi sains sebesar 66,7.